DEVELOPMENT OF A VERTICAL-AXIS WIND TURBINE DESIGN - Katkov, Valerii (Journal of Renewable Energy and Mechanics, 2025)
The article presents the development of a modernized vertical-axis wind turbine design aimed at improving energy efficiency by eliminating turbulent losses and optimizing aerodynamic characteristics. Key innovations include the implementation of a nozzle grid with a cosine-shaped profile to stabilize airflow, the use of rotor blades with confuser-diffuser geometry, and upgraded guide vanes. Results from computational modeling and wind tunnel tests confirmed a 57% increase in airflow velocity, reduced turbulence, a 5.3% improvement in efficiency, and enhanced structural stability. The system demonstrates potential for application in standalone power supply systems at low wind speeds (from 3 m/s).